Decarbonising economies - Bulkeley, Harriet 1972- (Cambridge University Press, 2022)
Based on an interdisciplinary investigation of future visions, scenarios, and case-studies of low carbon innovation taking place across economic domains, Decarbonising Economies analyses the ways in which questions of agency, power, geography and materiality shape the conditions of possibility for a low carbon future. It explores how and why the challenge of changing our economies are variously ascribed to a lack of finance, a lack of technology, a lack of policy and a lack of public engagement, and shows how the realities constraining change are more fundamentally tied to the inertia of our existing high carbon society and limited visions for what a future low carbon world might become. Through showcasing the first seeds of innovation seeking to enable transformative change, Decarbonising Economies will also chart a course for future research and policy action towards our climate goals. This title is also available as Open Access on Cambridge Core.